Lighting Beyond Illumination: The Creative Approach by Laide Nasir in the Performance of The Mammy Water’s Wedding: International Journal of Humanitatis Theoreticus. Vol. 4. (Issue 1) - Ekpo, Ekaette; Emasealu, Emmanuel; Nwafor, Friday (Afrischolar Discovery Repository (Annex), 2020)
Lighting is an essential part of theatrical performance that makes other elements of theatrical production visible. It is a sensitive and delicate part of any theatrical performance, which has a great influence on the audience since it depicts the mood, interprets the theme, and also dictates the actions as well as the acting area. That is why this study in a bid to explore, gathered its sample data from a lighting designer in a university-based theatre, by documenting on his techniques and concepts as used in a dramatic production, in other to draw other theatre practitioners to his amazing phenomenon in stage lighting. Unfortunately, the efforts of many of these lighting designers in Nigeria receive scant scholarly research whereas; they play a major role in any theatrical production. However, there are also many inadequacies that still hinder the creative ingenuity of these lighting designers, which include funding, poor technical nfacilities, lighting equipment, and even the provision of new technology by the theatre owners. This study adopts the qualitative research methodology, which combines research principles using a formal form of data collection encompassing practical fieldwork, analytical and documentary methods. A purposive technique was used in selecting the designer and his performance in view. The study also adopts Edward Gordon Craig’s and Adolphe Appia’s “Plasticity Theory” (PL) and Adolphe Appia’s “Exploration of Aesthetic Scenery in Performances Theory”. The study reveals that Laide Nasir uses suggestive realism or surrealism as his performance style. And from findings, the study recommends that adequat lighting equipment should be provided for institutions where theatre is being taught, so that students who have interests in learning theatre design can be exposed to high level of technology while in school. And also, conscious efforts should be made by designers and theatre scholars to document on the scenic design and stage lighting concepts, techniques and styles as applied in their performances.